2023
DOI: 10.3390/nu15020310
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Services to Improve Nutritional Intake and Reduce Food Waste: A Systematic Review

Abstract: Background and Aims: Patients’ nutritional intake is a crucial issue in modern hospitals, where the high prevalence of disease-related malnutrition may worsen clinical outcomes. On the other hand, food waste raises concerns in terms of sustainability and environmental burden. We conducted a systematic review to ascertain which hospital services could overcome both issues. Methods: A systematic literature search following PRISMA guidelines was conducted across MEDLINE, Web of Science, and Scopus for randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The crosssectional study conducted in Canada found that the room service implementation resulted in a notable rise in customer satisfaction, decreased food costs during breakfast and lunch, and reduced waste across all meals. Notably, there was a rise in the consumption of energy, protein, carbohydrates, and fats during the lunch period (Rinninella et al, 2023). Additionally, Dynesen et al (2021) found that participants consumed more of the food provided than the trolley model, particularly during the afternoon meal.…”
Section: Room Service Modelmentioning
confidence: 98%
See 4 more Smart Citations
“…The crosssectional study conducted in Canada found that the room service implementation resulted in a notable rise in customer satisfaction, decreased food costs during breakfast and lunch, and reduced waste across all meals. Notably, there was a rise in the consumption of energy, protein, carbohydrates, and fats during the lunch period (Rinninella et al, 2023). Additionally, Dynesen et al (2021) found that participants consumed more of the food provided than the trolley model, particularly during the afternoon meal.…”
Section: Room Service Modelmentioning
confidence: 98%
“…However, in general, it has been observed that the technique tends to either underestimate or overestimate the proportion of leftover food on a plate compared to the weighing method (Antasouras et al, 2023;Heighington-Wansbrough & Gemming, 2022;Ofei et al, 2019). This measurement frequently relies on subjective monitoring of patient food intake, such as estimating food intake through plate diagrams and employing diverse job roles as evaluators (Heighington-Wansbrough & Gemming, 2022;Papathanail et al, 2021;Rinninella et al, 2023). It is also affected by missing data, such as conflicting obligations of nursing personnel that result in hurried recordkeeping, unintentional mistakes, and administrative oversights, such as skipped meals and evaluators' failure to grasp the significance of monitoring (Heighington-Wansbrough & Gemming, 2022;Rinninella et al, 2023).…”
Section: Visual Estimationmentioning
confidence: 99%
See 3 more Smart Citations